Translation Quality of English Version of West Sumatra Tourism Brochure 2020 - Aprilia, Orlin; Fitrawati, Fitrawati (English Language and Literature, 2021)
The aim of this research is to analyse the translation quality of the English Version of West Sumatra tourism brochure 2020. It was carried by using descriptive method. Twenty-seven tourism brochures werestudied based on the translation quality assessment model which is developed by Nababan et al. (2012). After completing the analysis, it was found that that 21 texts (77.77%) are categorized in the accurate level, 6 texts (22.23%) are translated less accurately, and none of the texts is translated inaccurately. In terms of their acceptability, 17 texts (62.97%) are less acceptable, 9 texts (33.33%) are categorized in less acceptable level, and the other text (3.70%) is assessed as the unacceptable translation.In addition, 20 texts (74.08%) are readable, 5 texts (18.52%) are less readable. Meanwhile, the other 2 texts (7.4%) are not readable.The results of the translation quality show that the translation of West Sumatra tourism brochuresis mostly accurate, acceptable and readable.